2020
DOI: 10.1111/vcp.12838
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of thyroid hormone levels and plasma capillary zone electrophoresis in red‐eared sliders (Trachemys scriptaelegans) and map turtles (Graptemysspp.) depending on season and sex

Abstract: Background: Thyroid hormones and capillary zone electrophoresis are rarely studied in reptile medicine. Objectives:The goal of this prospective study was to establish RIs for plasma proteins and thyroid hormones, total tetraiodothyronine (tT4), free T4 (fT4), total triiodothyronine (tT3), and free T3 (fT3), as well as iodine blood levels in red-eared sliders (Trachemys scripta elegans) and map turtles (Graptemys spp.).Methods: Variables were measured over 1 ½ years to determine variations depending on sex and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…45,48,69,75,76 Additional studies in various reptile species have demonstrated the necessity of method-specific RIs with the use of CZE in Hermann's tortoise, green turtle, red-eared slider, map turtle, panther chameleon, and boa constrictor. 29,47,[77][78][79] Differences in alpha and beta globulins were also reported in the black-headed ibis, chicken, black kite, and racing pigeon. 46,80 It is not uncommon to discern multiple globulin fractions using CZE.…”
Section: Capillary Zone Electrophoresismentioning
confidence: 85%
“…45,48,69,75,76 Additional studies in various reptile species have demonstrated the necessity of method-specific RIs with the use of CZE in Hermann's tortoise, green turtle, red-eared slider, map turtle, panther chameleon, and boa constrictor. 29,47,[77][78][79] Differences in alpha and beta globulins were also reported in the black-headed ibis, chicken, black kite, and racing pigeon. 46,80 It is not uncommon to discern multiple globulin fractions using CZE.…”
Section: Capillary Zone Electrophoresismentioning
confidence: 85%
“…Many of these findings differ from those in other chelonians. Relative albumin was higher in female red-eared sliders ( Trachemys scripta elegans ) and map turtles ( Graptemys geographica ) [ 66 ], and absolute albumin was higher in female eastern box turtles [ 4 ]. Male loggerhead sea turtles had higher absolute and relative beta globulin concentrations, although there was a great deal of beta-gamma bridging indicating possible underlying disease processes in those individuals [ 10 ].…”
Section: Discussionmentioning
confidence: 99%